Kepler's philosophy and the new astronomy - Martens, Rhonda, 1964- (Princeton University Press, 2000)
Johannes Kepler contributed importantly to every field he addressed. He changed the face of astronomy by abandoning principles that had been in place for two millennia, made important discoveries in optics and mathematics, and was an uncommonly good philosopher. Generally, however, Kepler's philosophical ideas have been dismissed as irrelevant and even detrimental to his legacy of scientific accomplishment. Here, Rhonda Martens offers the first extended study of Kepler's philosophical views and shows how those views helped him construct and justify the new astronomy. Martens notes that since Ke.